Multi-location external workload profile in women`s basketball players. A case study at the semiprofessional-level - Gómez-Carmona, C.D.; Mancha-Triguero, D.; Pino-Ortega, J.; Ibáñez, S.J. (Sensors, 2021)
The external workload measured in one anatomical location does not determine the total load supported by the human body. Therefore, the purpose of the present study was to characterize the multi-location external workload through PlayerLoadRT of 13 semi-professional women`s basketball players, as well as to analyze differences among anatomical locations (inter-scapulae line, lumbar region, 2× knee, 2× ankle) and laterality (left vs. right) during five tests that represent the most common movements in basketball—(a) linear locomotion, 30-15 IFT; (b) acceleration and deceleration, 16.25-m RSA (c) curvilinear locomotion, 6.75-m arc (d) jump, Abalakov test (e) small-sided game, 10` 3 vs. 3 10 × 15-m. Statistical analysis was composed of a repeated-measures t-test and eta partial squared effect size. Regarding laterality, differences were found only in curvilinear locomotion, with a higher workload in the outer leg (p < 0.01; p2 = 0.33-0.63). In the vertical profile, differences among anatomical locations were found in all tests (p < 0.01; p2 = 0.56-0.98). The nearer location to ground contact showed higher values except between the scapulae and lumbar region during jumps (p = 0.83; p2 = 0.00). In conclusion, the multi-location assessment of external workload through a previously validated test battery will make it possible to understand the individual effect of external workload in each anatomical location that depends on the type of locomotion. These results should be considered when designing specific strategies for training and injury prevention.